Cervical cerclage and type of suture material: a survey of UK consultants' practice. (October 2014) - Israfil-Bayli, F.; Toozs-Hobson, P.; Lees, C.; Slack, M.; Daniels, J.; Vince, A.; Ismail, K. M. K.
Abstract Objective: The main aim of the survey was to explore current practices with regards to cervical cerclage procedures amongst UK consultants with particular emphasis on the type of suture material used. Methods: An electronic survey of UK consultant members and fellows of the Royal College of Obstetricians and Gynaecologists and who previously agreed to be contacted for survey purposes. Results: There were 261 respondents to the survey and 88% routinely performed cerclage. The majority performed the procedure between 12 and 16 weeks' gestation (88.7%; n = 180/203), following the McDonald technique (83.4%; n = 166/199) and using a braided suture material (86.6%; n = 175/202). Although only 27 of the 202 responders (13.4%) used a monofilament suture for cerclage (75%; n = 149/201) of clinicians stated that they were not sure what is the best suture material to be used. Conclusion: There is considerable variation in practice amongst Consultant obstetricians with regards to cervical cerclage. Although most respondents use the traditional braided suture material, a significant proportion of them were not sure what is the best suture material to use. The "gestation at delivery" rate was judged to be the most important outcome for a future study.